RICARDO’S MANIA LOVE IN MARIO VARGAS LLOSA’S THE BAD GIRL (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
RICARDO’S MANIA LOVE IN MARIO VARGAS LLOSA’S THE BAD GIRL Deny Dwi Susanti English Literature, Faculty of Languages and Arts, Surabaya State University ddwisusanti@yahoo.com Drs. Much. Khoiri, M.Si English Department, Faculty of Languages and Arts, Surabaya State University much_choiri@yahoo.com Abstrak Penelitian ini difokuskan pada cinta mania Ricardo dalam novel The Bad Girl oleh Mario Vargas Llosa. Cinta mania ditandai dengan emosi pada diri sendiri, upaya putus asa untuk memaksa kasih sayang dari sang kekasih, dan ketidakmampuan untuk percaya atau mempercayai kasih sayang yang dicintai sebenarnya. Pecinta mania adalah seseorang yang memiliki hiper ekspektasi yang terobsesi terhadap seseorang tanpa persetujuan tertentu diantara keduanya. Tujuan dari penelitian ini adalah untuk menggambarkan bagaimana cinta mania Ricardo tercermin dalam novel The Bad Girl oleh Mario Vargas Llosa, untuk mengungkapkan faktor-faktor apa yang membuat Ricardo memiliki cinta mania, dan untuk mengungkapkan dampak cinta mania Ricardo dalam novel. Penelitian ini menggunakan teori John Alan Lee dan Sternberg untuk menganalisis novel tersebut. Akhirnya, analisis penelitian ini menghasilkan tiga temuan. Temuan pertama adalah bahwa cinta mania yang dialami oleh Ricardo ini sejalan dengan jenis cinta yang dinyatakan oleh Lee dan Sternberg. Temuan kedua menunjukkan bahwa ada tiga faktor yang memicu cinta mania Ricardo; yaitu merasa sedih, kepercayaan diri yang rendah, dan kehidupan sosial yang buruk. Untuk temuan terakhir, ada tiga hal yang mempengaruhi kehidupan Ricardo yaitu efek fisik, efek psikologis, dan efek sosial. Efek-efek tersebut yang mempengaruhi Ricardo sebagai pecinta mania selama terobsesi terhadap gadis nakal. Kata Kunci: cinta mania, cinta obsesif Abstract This study focuses on Ricardo’s Mania Love in Mario Vargas Llosa’s The Bad Girl. Mania love is characterized by self-defeating emotions, desperate attempts to force affection from the beloved, and the inability to believe in or trust any affection the loved one actually does display. The manic lover is someone who has a hyper expectation to obsess a person without a certain aggreement on both sides. The purposes of the study were to describe how Ricardo’s mania love is reflected in Mario Vargas Llosa’s The Bad Girl, to reveal what factors make Ricardo have his mania love, and to reveal the impacts of Ricardo’s mania love in the novel. The study used John Alan Lee and Sternberg theories to analyze the novel. Eventually, this analysis of this study resulted in three findings. The first finding was that mania love which was experienced by Ricardo was in line with the types of love stated by Lee and Sternberg. The second finding showed that there were three factors which trigger the Ricardo’s mania love; namely feeling down, low self confidence, and poor social life. For the last finding, there were three things which affect Ricardo’s life. They were physical effect, psychological effect, and social effect. Those effects affected Ricardo as the manic lover as long as he obssessed for the bad girl. Keywords: mania love, obsessive love INTRODUCTION Love has always been a favorite topic for poets, novelists, and songwriters. It has always relationship with literature. And it is difficult to imagine literature without love. Love becomes so universal theme because of the remarkable variety of its world. Nothings else human being so impatically declares at the same time the plurality of living (Bayley in Mardianto, 2008:1). It is an emotion that nearly everyone has experienced in their life. Because the main purpose of life is to be happy and there is only happiness in life, that is love and to be loved. Literary work is a reflection of the real world. By studying the human literature we can also learn the real life world. It means to study the character of the same in the literature by studying real human character. Literary work presents a wide range of people including the possible odd or taboo if discussed. To learn it let us see the work of a famous writer Mario Vargas Llosa. Mario Vargas Llosa’s recent novel The Bad Girl centers around of love. Of course, there are a lot of literary work which uses love as the main theme. But, in this novel the reader will be brought to Ricardo’s love. Sobur said that love is a common thing in human being. Because everyone has through the love experienced in their life. And according to Watson that basically, human has three basic emotions. They are fear which can develop into anxiety, rage which can develop into anger, and love which can develop into sympathy. (Meliana, 2008:2). Everyone has an emotion to be developed, such as in anxiety, anger, or love. It depends on the people in driving their emotion. The Bad Girl is the novel which is translated by Edith Grossman, the winner of the 2006 PEN/Ralph Manheim Medal for Translation, is the translator of many works by major Spanish-language authors, including Gabriel García Márquez, Mayra Montero, and Miguel de Cervantes, as well as Mario Vargas Llosa. She lives in New York City. Additional praise for The Bad Girl, Chicago Tribune Favorite Book of 2007 and San Francisco Chronicle Notable Book of 2007.